Microvesicles in Atherosclerosis and Angiogenesis: From Bench to Bedside and Reverse - Badimon, Lina; Suades, Rosa; Arderiu, Gemma; Peña, Esther; Chiva-Blanch, Gemma; Padró, Teresa (Frontiers in Cardiovascular Medicine, 2017)
Atherosclerosis (AT) is a progressive chronic disease involving lipid accumulation, fibrosis and inflammation in medium and large-sized arteries and it is the main cause of cardiovascular disease (CVD). AT is caused by dyslipidemia and mediated by both innate and adaptive immune responses. Despite lipid-lowering drugs have shown to decrease the risk of cardiovascular events (CVE), there is a significant burden of AT related morbidity and mortality. Identification of subjects at increased risk for CVE as well as discovery of novel therapeutic targets for improved treatment strategies are still unmet clinical needs in CVD. Microvesicles (MVs), small extracellular plasma membrane particles shed by activated and apoptotic cells have been widely linked to the development of CVD. MVs from vascular and resident cells by facilitating exchange of biological information between neighboring cells serve as cellular effectors in the bloodstream and play a key role in all stages of disease progression. This article reviews the current knowledge on the role of MVs in atherosclerosis and cardiovascular disease. Attention is focused on novel aspects of MV-mediated regulatory mechanisms from endothelial dysfunction, vascular wall inflammation, oxidative stress and apoptosis to coagulation and thrombosis in the progression and development of atherothrombosis. MV contribution to vascular remodeling is also discussed, with a particular emphasis on the effect of MVs on the crosstalk between endothelial cells and smooth muscle cells, and their role regulating the active process of atherosclerosis-driven angiogenesis and neovascularization. This review also highlights the latest findings and main challenges on the potential prognostic, diagnostic and therapeutic value of cell-derived MVs in cardiovascular disease. In summary, microvesicles have emerged as new regulators of biological functions in atherothrombosis and might be instrumental in cardiovascular precision medicine, however significant efforts are still needed to translate into clinics the latest findings on microvesicle regulation and function.